Methods for chemical preparation of aflatoxin B1 adducts, AFB1-N7-guanine and AFB1-lysine. (24th October 2013) - Cristina Sass, Daiane; Vincenzi Jager, Alessandra; Gustavo Tonin, Fernando; Naira Zambelli Ramalho, Leandra; Silva Ramalho, Fernando; Gomes Constantino, Mauricio; Augusto Fernandes Oliveira, Carlos
Abstract: Aflatoxin B1 (AFB1 ) is a hepatocarcinogen produced by fungi species of the genus Aspergillus . Dietary exposure to AFB1 is associated with increasing incidence of hepatocellular carcinoma. The biotransformation of AFB1 generates the adducts AFB1 -N 7 -guanine and AFB1 -lysine, which are used as biomarkers of human exposure to dietary AFB1 in epidemiological studies. This article presents a review of main studies on the use of AFB1 adducts as biomarkers of human exposure to AFB1, and the current status of chemical procedures for the preparation of AFB1 -N 7 -guanine and AFB1 -lysine as analytical standards.